Non-classical conditional probability and the quantum no-cloning theorem. (11th August 2015) - Niestegge, Gerd
Abstract: The quantum mechanical no-cloning theorem for pure states is generalized and transfered to the quantum logics with a conditional probability calculus in a rather abstract, though simple and basic fashion without relying on a tensor product construction or finite dimension as required in other generalizations.